Shape matters: The application of activity‐based in vitro bioassays and chiral profiling to the pharmacological evaluation of synthetic cannabinoid receptor agonists in drug‐infused papers seized in prisons. Issue 3 (9th December 2020) - Antonides, Lysbeth H.; Cannaert, Annelies; Norman, Caitlyn; NicDáeid, Niamh; Sutcliffe, Oliver B.; Stove, Christophe P.; McKenzie, Craig
Abstract: Synthetic cannabinoid receptor agonists (SCRAs) elicit many of their psychoactive effects via type‐1 human cannabinoid (CB1 ) receptors. Enantiomer pairs of eight tert ‐leucinate or valinate indole‐ and indazole‐3‐carboxamide SCRAs were synthesized and their CB1 potency and efficacy assessed using an in vitro β‐arrestin recruitment assay in a HEK239T stable cell system. A chiral high‐performance liquid chromatography method with photodiode array and/or quadrupole time‐of‐flight‐mass spectrometry detection (HPLC‐PDA and HPLC‐PDA‐QToF‐MS) was applied to 177 SCRA‐infused paper samples seized in Scottish prisons between 2018 and 2020. In most samples, SCRAs were almost enantiopure ( S )‐enantiomer (>98% of total chromatographic peak area), although in some ( n = 18), 2% to 16% of the ( R )‐enantiomer was detected. ( S )‐enantiomers are consistently more potent than ( R )‐enantiomers and often more efficacious. The importance of SCRA‐CB1 receptor interactions in the "head" or "linked group" moiety is demonstrated, with the conformation of the "bulky" tert ‐leucinate group greatly affecting potency (by up to a factor of 374), significantly greater than the difference observed between valinate SCRA enantiomers. ( S )‐MDMB‐4en‐PINACA, ( S )‐4F‐MDMB‐BINACA, and ( S )‐5F‐MDMB‐PICA are currently the most prevalent SCRAs in Scottish prisons, and all have similar high potency (EC50, 1–5 nM) and efficacy. Infused paper samples were compared using estimated intrinsic efficacy at the CB1 receptor (EIECB1 ) to evaluate samples with variable SCRA content. Given their similar potency and efficacy, any variation in CB1 receptor‐mediated psychoactive effects are likely to derive from variation in dose, mode of use, pharmacokinetic differences, and individual factors affecting the user, rather than differences in the specific SCRA present. Abstract : The pharmacology of a group of 16 enantiopure carboxamide‐type SCRAs is examined and a chiral chromatography method to analyze a large group of seized prison samples is applied. The potency, efficacy, concentration, and enantiopurity of the individual SCRAs all contribute to the overall potency and efficacy of seized samples.